STUDENTS' ATTITUDES TOWARD LEARNING MANAGEMENT SYSTEM (LMS) DURING COVID-19 PANDEMIC: A CASE STUDY - Mundir, Mundir; Umiarso, Umiarso (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
This study aimed to know the students' attitudes and influenced factors in learning Islamic education using Learning Management System (LMS). This study used a qualitative approach based on the social cognitive theory. The subjects of this research were 18 students and 3 teachers who taught Islamic education online in SMA 1 Jember. Data were collected through observation, interviews, and documentation. The data were analyzed using Miles' and Hubermann's interactive technique, consisting of three stages: data condensation, presentation, and conclusion. The result of this research indicated that the students' attitudes in the implementation of LMS during learning Islamic education were positive because they could easily reach learning material and other sources. In addition, the students' attitudes on LMS were influenced by three factors: individual (e-learning self-efficacy), social (subjective norm), and organizational (accessibility system) factors. Abstrak: Penelitian ini bertujuan untuk mengetahui sikap siswa dan faktor-faktor yang mempengaruhinya dalam pembelajaran pendidikan Agama Islam menggunakan Learning Management System (LMS). Penelitian ini menggunakan pendekatan kualitatif berdasarkan Social Cognitive Theory. Subjek penelitian ini adalah 18 siswa dan 3 guru yang mengajar Pendidikan Agama Islam secara online di SMA Negeri 1 Jember. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Analisis data menggunakan teknik interaktif Miles dan Hubermann, yang terdiri dari tiga tahap: kondensasi data, penyajian, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa sikap siswa selama pembelajaran Pendidikan Agama Islam menggunakan LMS adalah positif karena mereka dapat dengan mudah menjangkau materi pembelajaran dan sumber lainnya. Selain itu, sikap siswa terhadap LMS dipengaruhi oleh tiga faktor: faktor individu (e-learning self-efficacy), sosial (subjective norm), dan faktor organisasi (accessibility system).